Structured Inquiry Learning: Enhancing Critical Thinking and Conceptual Understanding through Productive Questioning - Agustina Agustina; Roszelina Abd Rahman (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to examine the effect of structured inquiry learning based on productive questioning on students’ critical thinking skills and conceptual understanding of plant tissue structure in senior high school biology learning. Methodology: This study employed a quantitative quasi-experimental method using a non-equivalent control group design. Data were collected using critical thinking and conceptual understanding tests, observation sheets, and documentation. Statistical analyses included descriptive statistics, Kolmogorov–Smirnov normality test, Levene’s homogeneity test, N-gain analysis, independent sample t-test, and effect size calculation using SPSS software. Main Findings: The results showed significant differences between experimental and control groups in critical thinking and conceptual understanding. The experimental group achieved higher posttest scores, moderate-to-high N-gain values, and large effect sizes. These findings indicate that structured inquiry learning with productive questioning effectively improves students’ higher-order thinking and conceptual mastery. Novelty/Originality of this study: This study integrates productive questioning explicitly within a structured inquiry learning model and examines its simultaneous effect on critical thinking and conceptual understanding. This approach provides new empirical evidence on how productive questioning strengthens cognitive engagement and enhances learning outcomes in biology education contexts.